The Effect of Price, Sales Promotion and Personal Selling on the Daihatsu Sirion Purchase Decision at PT Capella Medan: The Effect of Price, Sales Promotion and Personal Selling on the Daihatsu Sirion Purchase Decision at PT Capella Medan - Sufika Sary; Trisha Aprila; Suryanto Suryanto (Institute of Computer Science (IOCS), 2020)
The purpose of this study was to analyze the effect of price, sales promotion and personal selling on the Daihatsu Sirion purchasing decision at PT Capella Medan. There was a decrease in purchasing decisions, reflecting the failure to achieve company targets due to prices, sales promotions and personal sales. The population in this study may be 230 consumers and the sample is considered to be 146 consumers. The sampling technique used was random sampling. The data analysis used was validity and reliability test, classical assumption test, linear multiple regression analysis, and hypothesis testing. The conclusion of the study shows that simultaneously and partially price, sales promotion and personal selling have a positive and significant effect on the purchasing decision of the Daihatsu Sirion at PT Capella Medan.